Crunch time for Korea's cloners - Cyranoski, David (Nature (London), 2004)
In Feb 2004, a research team in Seoul Korea announced that it had obtained embryonic stem cells from a cloned human embryo, providing a proof of principle for therapeutic cloning. Ethics questions are surrounding the research, relating to the recruitment of the women who donated eggs for the project and whether guidelines designed to protect their rights were correctly applied.